The Relationship Effect of Board Characteristics and Company Characteristics on Corporate Social Responsibility - Udipta, Rizky Prastya; Chandra, Kristian; Margaretha, Farah (Business and Entrepreneurial Review, 2024)
This study aims to analyze the influence of board characteristics on CSR policies with the company characteristics as control variables. CSR policy in this study focuses on the amount of CSR costs incurred by the company to contribute to the social and community environment. The data used in this study are secondary data sourced from the annual reports of energy sub-sector companies listed on the Indonesian Stock Exchange (BEI) from 2016-2022. The research sample was selected using the purposive sampling method, resulting in 28 companies as the sample. The data analysis used for hypothesis testing is multiple regression analysis using the Eviews 9 program. The results of the study indicate that board characteristics, as indicated by the variables of board size and firm age, have a significant positive influence on CSR. The results also show that firm size has a significant positive influence on CSR performance, while leverage has a significant negative influence on CSR performance. These findings provide information that the increasing number of board members in important positions within a company will impact the high CSR performance, as well as the maturity of a company indicated by the years since going public will enhance the high concern for the environment. In addition, the level of company leverage will be one of the considerations for investors in investing capital as it will have a negative impact on the adopted CSR policies.